Congenital Hypertrophy of the Right Ventricle Successfully Treated with Very Low Dose Beta Blockers - Emeis, Michael; Lunze, Fatima I; Miera, Oliver; Berger, Felix; Rossi, Rainer; Schmitt, Boris (Cardiology and Cardiovascular Medicine, 2020)
A late preterm baby girl presented with feeding problems and desaturation. Septic work-up was negative, however. Severe right ventricular cardiac hypertrophy is revealed by echocardiography. Based on recent scientific findings on cardiodynamics and the inner antagonism in myocardial architecture, the baby is treated with very low-dose beta blockers instead of higher standard dosage. The therapy leads to immediate improvement in right ventricular function and reduction of right ventricular hypertrophy. Oxygen supply could be stopped, normal feeding was possible. Here we report the first case of very low-dose beta blocker therapy in a neonate for resolution of myocardial inner antagonism.